Aplikasi Pencatatan Penggajian Dan Koperasi Di Lapas Narkotika Kelas II A Pangkalpinang - Syahputra, Abang Muhammad Fauzan; Fujiyanti, Linda; Josi, Ahmad (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The development of information technology has influenced various fields, including education. At the Babel State Manufacturing Polytechnic, the Merdeka Belajar Kampus Merdeka (MBKM) program aims to provide flexibility for students in choosing learning activities. However, the implementation of the program is often hampered by administrative problems, such as delays in submitting credit claims to the academic advisor. To overcome this, a web-based information system was developed that facilitates the process of claiming and recapitulating credits online. This study used the prototyping method with blackbox testing involving 13 respondents. The test results showed a user acceptance score (UAT) of 84.92%, indicating that this system is feasible to implement. With this system, students can submit claims and recap credits independently without depending on the presence of lecturers, thereby increasing the efficiency and transparency of credit management. The implementation of this system is expected to improve the quality of administrative services at the Babel State Manufacturing Polytechnic.